Psychological Aspects of the Quality of Life of Caregivers of the Elderly: An Integrative Review - Letícia Decimo Flesch; Samila Sathler Tavares Batistoni; Anita Liberalesso Neri; Meire Cachioni (Brazilian Society of Geriatrics and Gerontology, 2024)
OBJECTIVE: This article reviewed studies that relate aspects of double vulnerability (caregivers' physical health, caregivers' self-perceived health, care recipients' dependency and perceived burden) with psychological aspects of caregivers' quality of life. METHODS: The search was conducted in the PubMed, Capes, LILACS, SciELO and AgeLine indexes using keywords in English and their corresponding words in Portuguese. RESULTS: Twenty-three papers were analyzed. With regards to the methods, most articles were made up of transversal studies and included various outcomes. There was a wide age range for the caregivers in the studies' samples, and many of them presented incomplete information about age. CONCLUSION: The results showed that a caregiver's quality of life is affected by several simultaneous variables such as the degree and type of dependency of the elderly person receiving care, the caregiver's health, perceived burden, and positive and negative affects.